"CHIMYON" MOUNTAIN RANGE - Abdullayeva Ozoda Islom qizi; Husanov Farrux Nurmatulla o‘g’li; Bo‘riyev Bo‘ron Ikrom o‘g’li (Galaxy International Interdisciplinary Research Journal, 2023)
In the article, a number of opinions about the "Chimyon" mountain range from many mountain ranges are presented.